A survey of important decisions and settings needed for attaining a sustainable world - Larsson, Nils O. (Journal of Sociocybernetics, 2013)
The main objective of the methodology to be presented is to find the most important decisions within the area of discussion. Focussing on the important decisions and in which environment they are taken gives an increased possibility of solving the problems in question. The analysis should cover decisions on all levels i.e. individual, informal and formal groupings of people, nations, group of nations as well as decisions on the global level. In this paper I will present some examples that could serve as an elucidation of the method. The goal of the method is to outline a system for a sustainable control of global renewable as well as non-renewable resources such as cultivable soil, water, fish, clean air, minerals, and oil. In order to handle the complexity of the problem the analysis must be limited to the most important factors in a long as well as short time view. A number of factors to be used in describing the methodology is presented.  In order to simplify the finding of the decisions influencing an analysis of sub-factors is necessary.  Decisions having an important influence on the above factors are presented and the information needed for making relevant decisions.  The next step in the analysis is to create a decision hierarchy and what organizations should be responsible for taking these decisions.